The Impact of Board Composition on Firm Value Creation through Carbon Emission Activities - Yadikarsa, Kevin Indra; Ng, Suwandi (Magister Akuntansi - Universitas Atma Jaya Makassar, 2025)
The purpose of this study was to investigate the effect of board composition on the creation of firm value through carbon emission disclosure. Population used in the whole company non-financial listed in Indonesia Stock Exchange period 2019-2022. Number of sampels are 57 firms, was selected by purposive sampling method. The analytical method used is path analysis and Sobel test for hypothesis mediation analysis. The result of analysis show that board of director size, gender diversity of commissioner, and audit committee have positive and significant effect on carbon emission disclosure. While carbon emission disclosure have positive and significant effect on firm value. This research also show that the carbon emission disclosure do not mediate the effect of board of director size, gender diversity of commissioner, and audit committee on firm value. The implication is the firms should pay more attention to the company activities with the surrounding enviroment through the formation of board composition.